Schistosoma Infection and Schistosoma-Derived Products Modulate the Immune Responses Associated with Protection against Type 2 Diabetes - Tang, Chun-Lian; Liu, Zhi-Ming; Gao, Yan Ru; Xiong, Fei (Frontiers in Immunology, 2018)
Studies on parasite-induced immunoregulatory mechanisms could contribute to the development of new therapies for inflammatory diseases such as type 2 diabetes (T2D), which is a chronic inflammatory disease characterized by persistent elevated glucose levels due to insulin resistance. The association between previous Schistosoma infection and T2D has been confirmed—Schistosoma infection and Schistosoma-derived products modulate the immune system, including innate and acquired immune responses, contributing to T2D disease control. Schistosoma infections and Schistosoma-derived molecules affect the immune cell composition in adipose tissue, dampening inflammation and improving glucose tolerance. This protective role includes the polarization of immune cells to alternatively activated macrophages, dendritic cells, eosinophils and group 2 innate lymphoid cells. Furthermore, Schistosoma infection and Schistosoma products are effective for the treatment of T2D, as they increase the number of type 2 helper T cells (Th2) and regulatory T cells (Tregs) and decrease type 1 helper T cells (Th1) and type 17 helper T cells (Th17) cells. Thus, our aim was to comprehensively review the mechanism through which Schistosoma infection and Schistosoma products modulate the immune response against T2D.